Wind pressure characterization on ground-mounted solar PV systems: A combined experimental and numerical study - Krishna Debnath; Jagadish Barman; Chien-Chun Hsieh; Chao-Yang Huang; Rei-Cheng Juang; Chih-Wei Chiu; Chung-Feng Jeffrey Kuo (Case Studies in Thermal Engineering)
This study introduces a novel integrated methodology combining wind tunnel (WT) experiments, Computational Fluid Dynamics (CFD), and Finite Element Analysis (FEA) to thoroughly evaluate wind-induced effects on ground-mounted photovoltaic (PV) tracking systems. A full-scale numerical simulation alongside a detailed 1:100 scale wind tunnel experiment comprising 96 PV panels were conducted across twelve distinct wind directions (0°–330°). Experimental results indicated edge and corner panels experienced maximum pressure coefficients (Cp) of +1.0 at 0° and −0.5 at 180°, thus supporting the largest aerodynamic loads. CFD simulations validated these findings with high accuracy (RMSE <0.2), also replicating turbulence intensity (13 % at panel height). Structural analysis under critical wind (100.8 km/h) confirmed structural integrity, showing a maximum von Mises stress of 201.55 MPa, strain of 0.0012, and deformation of 6 mm, all safely below material limits (yield strength: 235 MPa). This study's main scientific contribution is the establishment of practical, verified design wind pressure coefficients for massive ground-mounted PV arrays, which closes a significant gap in current engineering standards. These insights significantly enhance structural optimization practices, ensuring material efficiency and reinforcing vulnerable panel zones, thereby contributing substantially to the resilience and economic sustainability of PV infrastructure under extreme wind conditions.